Selected examples of Muslim loyalism in the Balkans toward Christian states: The case of Bosnia‐Herzegovina and Bulgaria 1878–1914 - Popek, Krzysztof; Lis, and Tomasz Jacek (The Muslim world (Hartford), 2024)
The purpose of this article is to characterize the loyalist attitudes of Muslims in Bulgaria and Bosnia‐Herzegovina (then part of Austria‐Hungary) in the period between the Congress of Berlin and the outbreak of World War I, with particular focus on the issue of differences between the religious beliefs of these communities and the ruling religion of their respective states. The analysis was carried out based on selected examples using the case study method (attitudes toward armed resistance, military service, and the formation of elites in support of the state), and is preceded by a profile of the approach of the authorities in Bulgaria and Bosnia‐Herzegovina toward their Muslim subjects. By comparing the state‐citizen and citizen‐state attitudes, the article addresses the question concerning the degree of communal loyalty to the Christian authorities and – based on the comparative method – outlines the primary differences between the two.